Editorial (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
In this issue of Urdimento, it delivers to its readers and authors an important thematic dossier that dialogues with the concerns of the present time. This dossier was suggested by professors who, in addition to proposing the theme, forwarded it to the Editorial Committee, composed of representatives of their respective areas of knowledge.
Keywords: editorial